Cycloadditions with 2-Chloro-1-Nitroethylene - R. Verbruggen; H.G. Viehe (CHIMIA)
2-chloronitroethylene replaces successfully the still elusive unsubstituted nitroacetylene in both the 1,3-dipolar and Diels-Alder cycloadditions. These reactions generally afford interesting nitrated cyclic and heterocyclic compounds.